Effects of Imputation Ratio Change on Open Economy in the Integrated Income Tax System - Lai, Chung-Fu; Chang, Yin-Rong (Asian Economic and Financial Review, 2015)
In this paper, we investigate a representative individual who is both a consumer and a producer, and when the personal income tax of can be deducted from the paid corporate tax, how macroeconomic variables (e.g. consumption, output, price index, exchange rate, and terms of trade) are affected by change in imputation ratio with a New Open Economy Macroeconomics (NOEM) model. We found that when the imputation ratio reduces, price index will rise, consumption and output levels will fall, the exchange rate will remain unchanged, and the country size will determine the effect on terms of trade.